PENDIDIKAN KESEHATAN MENGENAI PENTINGNYA KONSUMSI TABLET TAMBAH DARAH DALAM UPAYA PENCEGAHAN ANEMIA PADA REMAJA - Wulandari, Anisa; Anita Natasya; Safanah, Ashila Nur; Febriana, Linda; Anugrah, Rikman; Aini, Yasinta Nurul; Dolifah, Dewi (LPPM UNINUS, 2024)
Anaemia is a disorder characterized by a decrease in Hb (haemoglobin) levels it should; in Indonesia, 32% of adolescents suffer from anaemia (3-4 out of 10 adolescents in Indonesia have anaemia). Adolescents who suffer from anaemia can experience changes in their ability to focus on learning, decreased levels of physical fitness, and growth problems that lead to abnormal height and weight. The Indonesian government has created a program in the form of iron supplementation aimed at adolescents through educational institutions to combat anaemia. In addition to assessing the impact of this health education activity on students' understanding and knowledge about the importance of TTD intake, this health education aims to increase students' understanding and knowledge about the urgency of drinking TTD in overcoming anaemia. This activity was carried out by a lecture method about the benefits of consuming TTD through PowerPoint and pamphlets and included the initial and final tests. Eight multiple-choice questions that measure knowledge of TTD are included in the test. The questions include the definition of TTD, the correct consumption technique, the benefits of TTD, the content of TTD, and ways to reduce the negative effects of TTD. The test assesses how much students know about blood-boosting supplements before and after attending health education. The result of this activity is that after receiving intervention in the form of health education, students' understanding increases as a result of this health education activity. Conclusion: Using educational resources such as PowerPoint and pamphlets, adolescents' understanding of TTD can be improved through health education about TTD. Keywords: Anemia, Health Education, Adolescents, Blood Tablets.